The experiences of employee well-being in the implementation of digital transformation in banking - Mayeza, Zukiswa (University of the Witwatersrand, Johannesburg, 2025)
Increasing reliance on digital tools in South African financial institutions, intensified by the COVID-19 pandemic, has raised significant concerns about the well-being and mental health of bank employees. As organisations progressively integrate digital tools—including remote work, advanced technologies, automation, and artificial intelligence—there is a growing concern regarding the psychological impacts on employees. This study explores how technological changes lead to work-related stress, anxiety, and burnout, particularly considering South Africa's unique socioeconomic and digital landscape. It is crucial to understand how these factors affect employees' well-being and find ways to mitigate them. The research involved conducting qualitative interviews with five participants from the South African bank, Bank A. The study employed thematic analysis to uncover important themes related to the psychological effects of digital transformation. The results indicate that employees face significant challenges, including technostress, digital burnout, and an imbalance between work and personal life. Furthermore, the report highlights several coping strategies employees utilise, such as mindfulness practices and family support, while emphasising the essential role of organisational support in alleviating these challenges. This study contributes to the limited research on employee well-being amid digital transformation, particularly in South Africa. The findings provide practical recommendations for organisations that foster healthier work environments through enhanced mental health support, flexible working hours, and wellness initiatives. Considering the rapid pace of digital change, this research underscores the necessity of a balanced strategy that values technological progress and employee well-being to ensure sustainable success for organisations. Moreover, this study advocates for a comprehensive approach that is not solely focused on technologies but also considers colleagues and the broader business context.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; digital transformation; employee well-being; mental health; SDG-8: Decent work and economic growth; SDG-9: Industry, innovation and infrastructure